Oncology Critical Care - Hoag, Jeffrey B. (IntechOpen, 2016)
According to the American Cancer Society, more than 1.6 million people will be diagnosed with cancer during this year. Outcomes have steadily risen over the last several decades with the advent of newer therapies. As outcomes have improved, more and more cancer patients are developing critical illness. In the not-too-distant past, patients with active malignancy were thought not appropriate for critical care services as decreased longevity related to the cancer suggested poor prognosis for intensive care utilization. More recently, evidence supports rapid activation of critical care services leading to improved outcomes in cancer patients. Moreover, just as sub-subspecialty critical care experience in trauma and neurosciences has proved beneficial, the emerging field of oncology critical care warrants specific attention.